Central neural contribution to the perception of chest pain in cardiac syndrome X. Issue 6 (1st June 2002) - Rosen, S D; Paulesu, E; Wise, R J S; Camici, P G
Abstract : Objective: To investigate the central neural contribution to chest pain perception in cardiac syndrome X (angina-like pain, ECG changes during stress, angiographically normal coronary arteriogram). Subjects: Eight syndrome X patients and eight healthy volunteers. Methods: Dobutamine stress using echocardiography to assess myocardial function, and positron emission tomography to measure changes in regional cerebral blood flow, as an index of neuronal activity. Results: During similar doses of dobutamine, syndrome X patients and controls showed comparable regional cerebral blood flow changes in the hypothalamus, thalami, right orbito-frontal cortex, and anterior temporal poles, associated with the sensation of a fast or powerful heart beat. In patients, but not controls, the stress also generated severe chest pain associated with increased activity in the right anterior insula/frontal operculum junction. There were ischaemia-like ECG changes in the syndrome X patients, but no left ventricular dysfunction on echocardiography. Activation of the right insula during chest pain clearly distinguished the syndrome X patients from a group of patients with known coronary disease. Conclusions: Chest pain and ECG changes were not accompanied by demonstrable myocardial dysfunction in syndrome X patients, but altered central neural handling of afferent signals may contribute to the abnormal pain perception in these patients.